Urbanization Alters Swimming Performance of a Stream Fish - Kern, Elizabeth M. A.; Langerhans, R. Brian (Frontiers in Ecology and Evolution, 2019)
Human activities cause many changes in wildlife populations, including phenotypic shifts that represent adaptations to new conditions and influence population dynamics, diversity, and persistence. Although many examples of phenotypic adjustment to anthropogenic disturbance exist, we rarely know the extent to which these changes result from genetic evolution or phenotypic plasticity. Furthermore, our understanding of how whole-organism performance changes as a result of habitat alteration is very limited. We tested how urbanization, an important type of global disturbance, influences fish swimming performance in urban streams. Because urban streams have higher water velocities during rain events than rural streams, we tested for increased steady-swimming performance in fish from urbanized watersheds. Across ten populations of wild-caught Creek Chub (Semotilus atromaculatus), we found that fish from streams in more urbanized areas exhibited a longer propulsive wavelength and a lower tailbeat frequency, expending lower levels of hydromechanical power during steady swimming. In a laboratory experiment, we reared individuals collected as fry from four populations with different urbanization histories, and found evidence for genetically based differences in swimming kinematics. Laboratory-reared fish derived from urbanized populations exhibited higher locomotor efficiency, matching predictions for adaptation to urban environments. We exposed laboratory-reared Creek Chub from urban and rural populations to artificially increased water velocity for four months and observed that only some populations exhibited plasticity. Urban populations may have lost maladaptive, velocity-induced plasticity in locomotor efficiency that is still present in rural populations. Evolutionary change in freshwater species may represent a widespread yet unrecognized consequence of anthropogenic activity.